PENGUNGKAPAN DIRI DITINJAU DARI DUKUNGAN SOSIAL TEMAN SEBAYA PADA MAHASISWA TAHUN PERTAMA UNIVERSITAS DIPONEGORO - Ryani Nugrahwati; Kartika Sari Dewi (Faculty of Psychology, Diponegoro University, 2014)
Self-disclosure is the individual ability for sharing personal information, including thought, feeling, experience, opinion, and respond to others. This study aims to know about relationship between peer social support with self-disclosure on the first-year college student of Diponegoro University. Subjects of this study were first-year college students of Diponegoro University, in amount 7838. Sampling technique was two stages cluster sampling, so that the samples were 336 people. Collecting data used two scales, namely Self-Disclosure and Peer Social Support Scale. Analyzing data used a simple regression analysis. The results showed that there is a positive relationship between peer social support with self-disclosure. It means that higher score of peer social support influences higher score of self-disclosure. Conversely, the lower score of peer social support makes the lower score of self-disclosure. Peer social support contributes effectively 32% of the self-disclosure.